Samospevi Marijana Lipovška - Nagode, Aleš (Glasbenopedagoški zbornik (Ljubljana), 2011)
The author sums up the presentation of Marijan Lipovšek's compositions for voice and piano, circumstances and chronology of their origin, musical characteristics and their interrelations with Slovenian creativity in music of the 20th century.
Keywords: 20.st.; 20th century; Lipovšek, Marijan; samospevi; Slovenia; Slovenian music; Slovenija; slovenska glasba; slovenski skladatelji; solo song